Derivative Claim in the System of Remedies for Corporate Legal Relations - KOSTRUBA, Anatoliy (Revista Jurídica Portucalense, 2023)
Corporate law has a lot of gaps and shortcomings in the legal doctrine to date. Therefore, it is important to find these shortcomings and propose solutions to eliminate them. The topic of this research includes a derivative claim which ensures the restoration of any person's rights and interests as a party to corporate legal relations. The theoretical and methodological basis includes dialectical, historical, and comparative methods used to study the establishment, development, and functioning of economic entities. The study identified key trends that have emerged in the area of redressing corporate rights, as well as the advantages and disadvantages of applying a derivative claim and the efficiency of the system for redressing the rights of subjects of corporate legal relations. Based on the analysis of the provisions of the world current legislation and experience describing the development of corporate legislation and corporate legal relations, the study identified main trends that have developed in this area, as well as the positive and negative aspects of the application of a derivative claim, and the effectiveness of the system for remedying the rights of subjects of corporate legal relations.